2000
DOI: 10.1210/jcem.85.4.6509
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropins and Cytokines Affect Luteal Function through Control of Apoptosis in Human Luteinized Granulosa Cells

Abstract: The luteal phase in the normal human menstrual cycle is known to be about 14 days. The physiological mechanisms that regulate the corpus luteum remain to be clarified, although apoptosis is reported to be involved. This study was undertaken to investigate the regulation of luteal function by gonadotropins, cytokines, and PGs, concentrating attention on the incidence of apoptosis and its molecular mechanisms in cultured human luteinized granulosa cells collected at oocyte pick-up from patients undergoing in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 39 publications
4
29
0
2
Order By: Relevance
“…Other known apoptosis inductive agents are androgens and GnRH [17,18]. On the other hand, the agents that have antiatretogenic effects are estrogens, FSH, LH and HCG [17,19]. The women in our study were stimulated with recombinant FSH that is supposed to posses an antiatretogenic effect Springer and GnRH antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Other known apoptosis inductive agents are androgens and GnRH [17,18]. On the other hand, the agents that have antiatretogenic effects are estrogens, FSH, LH and HCG [17,19]. The women in our study were stimulated with recombinant FSH that is supposed to posses an antiatretogenic effect Springer and GnRH antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that prolactin can stimulate TGF-b2 expression in rat luteal macrophages (Matsuyama et al 1990). Human granulosa-lutein cells treated with TGFb1 showed a significant reduction in apoptosis (Matsubara et al 2000). Therefore, it appears that TGF-b isoforms in concert with prolactin have the potential to support the CL by enhancing progesterone production and suppressing apoptosis.…”
Section: Ovulation Luteinization and CL Formationmentioning
confidence: 97%
“…An immunohistochemical study showed that human granulosa cells express hCG receptors (46). It is also well established that when gonadotropins, such as LH, FSH, and hCG, added to human granulosa luteal cells in culture affect luteal function through control of apoptosis (47). The role of hCG in luteal rescue has been attributed to up-regulation of a tissue inhibitor of metalloproteinase by human granulosa luteal cells (48) or down-regulation of P 2Y receptor message in human granulosa luteal cells (49).…”
Section: F I G U R Ementioning
confidence: 99%